Sistem Pendukung Keputusan Penentuan Program Keluarga Harapan di Dinas Sosial Kabupaten Sumba Barat Menggunakan Metode Naïve Bayes - Selvinus Dakku; Vinsensius Aprila Kore Dima; Diana Reby Sabawaly (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2025)
The Family Hope Program (PKH) is a conditional social assistance program provided by the government to improve the quality of life of underprivileged families through support in the education, health, and social welfare sectors. In its implementation, the process of determining PKH candidate recipients at the West Sumba Regency Social Service often experiences obstacles, especially with regard to objectivity, accuracy of targets, and limitations in complex data management. Thus, a decision support system (SPK) is needed that can assist the agency in selecting prospective recipients more effectively, efficiently, and on target. This study proposes the application of the Naive Bayes method in the development of SPK to determine PKH recipients. The Naive Bayes method was chosen because of its ability to classify data based on probability, and it can handle large volumes of data with a good degree of accuracy. The criteria applied in the classification include the level of household income, the number of members covered, the state of residence, the education of children, and the health of family members. The research process includes needs analysis, system design, data collection, application of Naive Bayes algorithms, and system testing. The findings of the study show that SPK based on Naive Bayes can provide recommendations for PKH recipients with better accuracy compared to manual methods. In addition, the system is able to improve transparency, fairness, and speed in the recipient selection procedure. With this system, it is hoped that the distribution of PKH in West Sumba Regency can be more orderly, balanced, and on target in accordance with the goals of government programs.